Israel's Hand in Guatemala's Genocide (Consortiumnews, 2014)
From the Archive: As world leaders struggle to praise the late Israeli Prime Minister Ariel Sharon, infamous for abetting the 1982 massacre of Palestinian civilians at Sabra and Shatila in Lebanon, another grim chapter of Sharon’s history was his role in the Guatemalan genocide, Robert Parry w